PENDAMPINGAN PENGEMBANGAN DAN PROMOSI UMKM WAYANG KERTAS DI WIRUN, MOJOLABAN, KABUPATEN SUKOHARJO - Puri, Anindita Dewangga; Baskoro, Aji Cahyo; Halim, Chandra (Universitas Sanata Dharma, 2025)
The existence of ‘Mbah Brambang’ paper puppets has become a valuable cultural asset for Wirun Village in Mojolaban, Sukoharjo Regency. Puppet craftsmen face economic challenges in the modern era as sales competition is carried out through online platforms. However, they are not very proficient in conducting online sales and primarily rely on offline transactions. It creates an effect such as declining online sales and a lack of offline customer presence. Addressing these challenges, the community service team provides training and assistance in increasing online sales and tips for increasing offline sales so that the existence of UMKM wayang kertas, which has been around for a long time, continues to exist. The community service was carried out through presentations, discussions, and demonstrations of the use of Shopee sales media. As a result, the puppet craftsmen now have an online shop on Shopee platform, and they are collaborating with the local youth group to jointly create a documentary video related to the history of the paper puppet’s existence. The use of Shopee as an online sales tool was also monitored and assisted by the community service team for several months, thus any difficulties could be immediately resolved. In this way, the craftsmen do not experience certain obstacles in online sales activities.